Desain dan Evaluasi Teknis Mesin Pengupas Kulit Kacang Macadamia (Macadamia integrifolia) PTR-TETA20 - Ruland Rantung; Dedie Tooy; Putri Amelia; Lucia Cecilia Mandey (Postgraduate, University of Mataram, 2025)
Macadamia (Macadamia integrifolia) is a high-value crop not widely known in Indonesia and still processed using conventional shelling methods that are time-consuming and inefficient. This study aimed to design and evaluate the PTR-TETA20 macadamia nut sheller to improve post-harvest efficiency. The research was conducted from May to July 2024 at the Faculty of Agriculture, Sam Ratulangi University. The methodology involved the design, construction, and performance testing of the machine using experimental methods and descriptive data analysis. The PTR-TETA20, measuring 30 × 23 × 113 cm and powered by a 1/4 HP motor with a pulley and V-belt system at 1467 RPM, was tested using 1 kg of macadamia nuts in three repetitions. The average working capacity reached 38.43 kg/hour, with a yield of 92.52%. Nut integrity was recorded as 40.22% whole, 36.10% halved, and 23.66% broken. Moisture content was 2.6% (whole), 2.56% (halved), 2.83% (broken), and 9.52% (shells). The results indicate that PTR-TETA20 offers a practical shelling solution for small-scale producers. However, machine performance can be improved by optimizing roller spacing and ensuring uniform nut drying.